Social determinants of ambulatory care sensitive conditions: a qualitative meta-synthesis based on patient perspectives - Chen, Hsueh-Fen; Lin, Hung-Ru (Frontiers in Public Health, 2023)
Background: Hospitalizations or emergency department (ED) visits due to ambulatory care-sensitive conditions (ACSC) are preventable but cost billions in modern countries. The objective of the study is to use a meta-synthesis approach based on patients’ narratives from qualitative studies to reveal why individuals are at risk of ACSC hospitalizations or ED visits. Methods: PubMed, Embase, Cochrane Library, and Web of Science databases were utilized to identify qualified qualitative studies. The Preferred Reporting Items for Systematic Review and Meta-Analysis were used for reporting the review. The thematic synthesis was used to analyze the data. Results: Among 324 qualified studies, nine qualitative studies comprising 167 unique individual patients were selected based on the inclusion/exclusion criteria. Through the meta-synthesis, we identified the core theme, six major themes, and their social risk factors. Poor disease management, the core theme, turns individuals at risk of ACSC hospitalizations or ED visits. The six major themes contribute to poor disease management, including missing appointments, non-compliance with medications, difficulties managing the disease at home, the burden of chronic disease, poor relationships with providers, and lack of patient-centered care. Notably, unstable housing, one of the social risk factors, contribute to four themes: missing appointment, non-compliance with medication, difficulties with managing the disease at home, and poor relationship with providers. Conclusion: Without addressing upstream social determinants, socially vulnerable patients are unlikely to manage their disease well at home even though they know how to do it and are willing to do it. Trial registration: National Library of Medicine, with ClinicalTrials.gov Identifier: NCT05456906. https://clinicaltrials.gov/ct2/show/NCT05456906